Can a higher endometrial thickness threshold exclude endometrial cancer and atypical hyperplasia in asymptomatic postmenopausal women? A systematic review. (7th January 2022) - Li, Jessica X. L.; Chan, Felix; Johansson, Cherynne Yuin Mun
Abstract : Background: Asymptomatic postmenopausal women incidentally found to have thickened endometrium (>4 mm) on transvaginal ultrasound (TVUS) often undergo hysteroscopy and dilatation and curettage despite having a low absolute risk of endometrial cancer. A low threshold for investigation may be unnecessary in these women. Aim: This systematic literature review examines whether an increased TVUS endometrial thickness threshold has superior diagnostic accuracy for endometrial malignancies and premalignancies in asymptomatic postmenopausal women than the current threshold of ≥4 mm. Methods: Pubmed, EMBASE and Cochrane Database of Systematic Reviews were systematically searched using keywords for publications between 2011 and 2021. Studies were included if they reported TVUS endometrial thickness analysis in asymptomatic postmenopausal women and excluded if they were written in a non‐English language. Quality of evidence in the included articles was evaluated according to recommendations by the Grading of Recommendations Assessment Development and Evaluation Working Group and reported results were tabulated. Results: Of seven studies ( N  = 2986), better evidence identified 12 mm as the optimal diagnostic threshold (area under the curve receiver operating characteristic (AUC ROC) 0.716, 95% CI 0.534–0.897, P  = 0.019) for endometrial cancer in asymptomatic postmenopausal women. Two higher quality studies ( n  = 488 and n  = 4751) identified 11 mm as optimal for diagnosing both endometrial carcinoma and atypical hyperplasia (AUC ROC 0.587, 95% CI 0.465–0.708, P  = 0.144 and 2.59 relative risk, 95% CI 1.66–4.05, P  < 0.001). Conclusion: Evidence for improved detection of endometrial premalignancies and malignancies using alternative endometrial thickness thresholds is not rigorous. Evidence for improved outcomes using alternative thresholds is inadequate. Observation of asymptomatic postmenopausal women without risk factors and with an endometrial thickness of less than 10 mm may be reasonable.